Career path of the three dancers from the province of Cabanatuan City, Nueva Ecija. - Comia, Joyce Aura Khristine Nazarena T.
This study presents the career paths of three dancers from the province of Cabanatuan City, Nueva Ecija. ill discuss their life from the day they started to dance until they found their careers.